A Green-IoT Healthcare and Agriculture Application (International Journal of Innovative Research in Computer Science & Technology, 2021)
In the fields of agriculture and  healthcare, the usage of two very common prominent and  emerging technical knowledge, Cloud Computing i.e., CC  in short and the Internet of Things or IoT in short, is  currently a trending topic. Motivated by a desire to create  a more ecological world, the authors in the paper  examines a number of technological aspects and concerns related to eco-friendly CC and IoT, and expands on the  argument by examining the fall of electric power intake of the two listed techniques when used together either in  farm or health related work. It will be addressed in the  paper - the idea of the ecological ICTs (Information and  Communications Technologies) and its past that are responsible for empowering Green-IoT. Eco-friendly or  green computing is introduced initially, followed by a  discussion of current research on the discussed two very  fast developing knowledges in farming and medical care.  Furthermore, this article adds by proposing a sensor cloud integration paradigm for Green-IoT Healthcare and  Agriculture Application (GHAA). Finally, the benefits,  difficulties, and future research prospects for green
Keywords: Agriculture Application; Cloud Computing; Green-IoT; Healthcare Application; Internet of Things; Sensor-Cloud